The doctrine of restraint of trade. An overview of its application in Malaysia / Timah Husin - Husin, Timah (Faculty of Law, 1987)
An agreement in restraint of trade is defined as one in which a person, for example an employee or the vendor of a business, agrees with the other contracting party to restrict his rights of trade freely or to offer himself on the employment market for some period after the completion of the sale or of his employment. As a general rule, all contracts restraining a person from carrying on a lawful profession, trade or business of any kind is to that extent prima facie void. To become valid they must be reasonable, both as between the parties themselves and in the public interest. Section 28 of The Contracts Act 1950 (Revised 1974 states that "Every agreement by which anyone is restrained from exercusing a lawful profession, trade or business of any kind, is to that extent void. However, there are three exceptions under section 28 of The Contracts Act 1950.